1997
DOI: 10.1143/jjap.36.l1211
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Helical Polysilane Nanostructures by Atomic Force Microscopy

Abstract: The nanostructure of a single quantum wire of the silicon: poly[n-decyl-(S)-2-methylbutylsilane] molecule on a hydrophobic ultrasmooth sapphire plate has been observed by atomic force microscopy (AFM). The backbone structure of this molecule is considered to be a rigid rodlike helix and to be fixed securely into a preferential single-screw-sense. The obtained result of the AFM shows that the polysilane molecule, with a length of about 2 µm, consists of very long rod-like segments linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…[10][11][12][13] Recently, several conformational kinks in 2's single molecule on sapphire are actually visualized by atomic force microscopy. 20 Such a conformational shrinkage associated with solvent polarity, also, is expected from the following FLA data. Figure 11 displays FLA data monitored at an emission peak wavelength along with UV absorption spectra of 1 at 23°C in four different mixed ethanol/water solvents.…”
Section: Solvent Effect Of Helical Conformation In a Mixedmentioning
confidence: 54%
See 1 more Smart Citation
“…[10][11][12][13] Recently, several conformational kinks in 2's single molecule on sapphire are actually visualized by atomic force microscopy. 20 Such a conformational shrinkage associated with solvent polarity, also, is expected from the following FLA data. Figure 11 displays FLA data monitored at an emission peak wavelength along with UV absorption spectra of 1 at 23°C in four different mixed ethanol/water solvents.…”
Section: Solvent Effect Of Helical Conformation In a Mixedmentioning
confidence: 54%
“…[15][16][17][18][19][20] The high ␣ value is typical for a rodlike polymer. For example, 2's in dilite solution at room temperature give extremely narrow CD, UV, and FL spectra near 320 nm, typically 7-8 nm of full width at half-maximum (fwhm).…”
mentioning
confidence: 99%
“…[112 -115] Ebihara et al succeeded in obtaining the first molecular AFM images of 7 single molecules with a very high molecular weight sample (M -w = 5 330 000, M -n = 4 110 000), deposited on an ultraflat hydrophobic sapphire surface ( Figure 6). [67] It was found that, although the total molecular contour image of 7 reached about 2 000 nm in length, the chain consisted of several segments separated by kinks. The individual long segment structures appear be rod-like with very slight structural fluctuations.…”
Section: Imaging Of Rod-like Polysilylene Single Moleculeseeing Is Bementioning
confidence: 99%
“…45 To avoid complexities as mentioned above, observation of intrinsic photoresponse of the monolayer isolated ideally to a single chain level is highly desired. Segregation to the level of the single polymer involvement may be achieved by high dilution of solutions 46 or in Functions of Azobenzene-containing Polymers monolayers. 47 For 6Az10-PVA monolayer, however, the lipophilic long side chain strongly promotes aggregation and prohibits isolation to a single chain.…”
Section: Visualization Of Polymer Motions By Microscopic Observationsmentioning
confidence: 99%